Incidence of Lung Adenocarcinoma Biomarker in a Caribbean and African Caribbean Population. Issue 5 (May 2016) - Leduc, Nicolas; Ahomadegbe, Christelle; Agossou, Moustapha; Aline‐Fardin, Aude; Mahjoubi, Linda; Roget, Leïla Dufrenot‐Petitjean; Grossat, Nathalie; Vinh‐Hung, Vincent; Lamy, Aude; Sabourin, Jean‐Christophe; Molinié, Vincent
ABSTRACT : Introduction: : Lung cancer is the leading cause of cancer deaths in the United States and worldwide. Biomarker testing is critical to personalized therapy in lung adenocarcinoma and has been extensively investigated in whites and Asians. However, little information addresses the underlying genetic changes among Caribbean and African Caribbean patients. In this study, we identified targetable biomarkers in Caribbean patients with lung adenocarcinoma. Methods: : DNA extracted from lung adenocarcinoma specimens collected from 157 patients in whom primary lung adenocarcinoma was diagnosed from 2013 to 2015 in the University Hospital of Martinique was tested for mutation of the epidermal growth factor receptor gene ( EGFR ), Kirsten rat sarcoma viral oncogene homolog gene ( KRAS ), B‐Raf proto‐oncogene, serine/threonine kinase gene ( BRAF ), phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha gene ( PIK3CA ), ROS proto‐oncogene 1, receptor tyrosine kinase gene ( ROS ), and MMNG HOS Transforming gene ( MET ). Clinical characteristics of our patients have been retrospectively gathered and correlated with mutational status. Results: : Mutations in EGFR were identified in 57 cases (36%). Women accounted for 68% of patients with mutations versus 38% of those without mutations ( p < 0.001). Eighteen percent of patients with mutations were smokers versus 62% of patients without mutations ( p < 0.001). Sex, smoking habit, and age were significantly associated with differences in mutational status in univariate analysis, and the difference remained statistically significant in multivariate analysis ( p = 0.0411, p = 0.001, and p = 0.0483, respectively). After the analysis was restricted to patients born in the French West Indies, the mutation rates reached 41%. Conclusion: : Patients in Martinique, and specifically those of African descent, show very high levels of EGFR mutation as opposed to what can be found in mainland France or in African Americans. These findings may be ascribed to low tobacco consumption as well as to genetic factors. Systematic screening in patients of African Caribbean origin should be prescribed.